Selective suppression of {112} anatase facets by fluorination for enhanced TiO2 particle size and phase stability at elevated temperatures. Issue 21 (29th September 2021) - Kohlrausch, Emerson C.; dos Reis, Roberto; Lodge, Rhys W.; Vicente, Isabel; Brolo, Alexandre G.; Dupont, Jairton; Alves Fernandes, Jesum; Santos, Marcos. J. L.
Abstract : Fluorinated ionic liquids are used to finely control the exposure of {112} facets on the TiO2 surface enabling an exquisite temperature control of the anatase-to-rutile phase transition. Abstract : Generally, anatase is the most desirable TiO2 polymorphic phase for photovoltaic and photocatalytic applications due to its higher photoconductivity and lower recombination rates compared to the rutile phase. However, in applications where temperatures above 500 °C are required, growing pure anatase phase nanoparticles is still a challenge, as above this temperature TiO2 crystallite sizes are larger than 35 nm which thermodynamically favors the growth of rutile crystallites. In this work, we show strong evidence, for the first time, that achieving a specific fraction (50%) of the {112} facets on the TiO2 surface is the key limiting step for anatase-to-rutile phase transition, rather than the crystallite size. By using a fluorinated ionic liquid (IL) we have obtained pure anatase phase crystallites at temperatures up to 800 °C, even after the crystallites have grown beyond their thermodynamic size limit of ca. 35 nm. While fluorination by the IL did not affect {001} growth, it stabilized the pure anatase TiO2 by suppressing the formation of {112} facets on anatase particles. By suppressing the {112} facets, using specific concentrations of fluorinated ionic liquid in the TiO2 synthesis, we controlled the anatase-to-rutile phase transition over a wide range of temperatures. This information shall help synthetic researchers to determine the appropriate material conditions for specific applications.